First-line biologic therapy with tumor necrosis factor inhibitors for psoriatic arthritis: a prospective observational study - Silva, Michael Ruberson Ribeiro da; Santos, Jéssica Barreto Ribeiro dos; Kakehasi, Adriana Maria; Almeida, Alessandra Maciel; Pimenta, Pedro Ricardo Kömel; Alvares-Teodoro, Juliana; Acurcio, Francisco de Assis (São Paulo Medical Journal, 2022)
BACKGROUND: Psoriatic arthritis (PsA) is a chronic inflammatory disease that affects multiple joints. It is associated with psoriasis and treated with synthetic and biologic drugs. OBJECTIVE: The objective of this study was to assess the outcomes of patients who received biologic therapy with tumor necrosis factor (TNF) inhibitors in terms of effectiveness, safety, functionality, and quality of life. DESIGN AND SETTING: A prospective observational study was performed at a single center in Belo Horizonte, Brazil. METHODS: Patients with PsA who received their first TNF inhibitor treatment were followed up for 12 months. Disease activity was measured using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Clinical Disease Activity Index (CDAI). Functionality was measured using the Health Questionnaire Assessment (HAQ), and quality of life was evaluated using the European Quality of Life Five Dimensions (EQ-5D). Multiple linear regression was used to identify predictors of the clinical response at 12 months. RESULTS: A total of 143 patients treated with adalimumab or etanercept were evaluated. Most of the clinical measures were significantly improved at 12 months. However, 31%–51% of the patients did not achieve good clinical control. No differences were observed between adalimumab and etanercept, except for poor functionality at 12 months among patients treated with etanercept. The main predictors of a worse clinical response were female sex, etanercept use, poor functionality, or lower quality of life at baseline. The main adverse reactions were alopecia, headache, injection site reaction, sinusitis, flu, dyslipidemia, and infections. CONCLUSION: TNF inhibitor therapy was effective and safe. However, despite improvements in clinical measures, most patients did not achieve satisfactory control of the disease.